A Study of Phonological Variations in the Baghdadi Arabic Dialect (Mesopotamian Journal of Arabic Language Studies, 2026)
This study investigates the role of phonology in language variation at local/native, (vernacular) national, and international levels. These variations in language may occur for the need of the speaker to reduce the difficulties of sound articulation in some speech positions. As a result, Arabic has various dialects that are spoken in different Arabic countries. The Baghdadi dialect is one of these variations which has its own rules and conditions. This study deals with important phonological issues related to the Baghdadi dialect which is one of the common dialects in Iraq. The study looks at the definitions of phonology, Arabic Phonology, and the Baghdadi dialect of Arabic at the segmental level as well as the similarities and differences between these two dialects. It also considers vowels of Arabic phonology and the Baghdadi dialect (monophthongs and diphthongs), and the consonants of the two dialects. The similarities and dissimilarities of sounds in the two dialects, problematic phonetic system symbols/sounds, voiced consonants, voiceless consonants and plosive consonants in the two languages are considered. The purpose of this study is to trace the phonological variations in the Baghdadi dialect and how far this dialect differs from Standard Arabic (MSA). This paper concludes that the phonological variations in the Baghdadi dialect result from one of three processes, either replacing, omitting, or inserting some sounds, and these phonological variations have two forms: either they have their origin in classical Arabic (CL), and this type follows specific rules, or they don’t have specific rules and depend on hearing